PENGARUH PEMBERIAN AMELIORAN DAN JUMLAH CACING TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU (Vigna radiata L.) - Soviyan Hajiz; Wardati Wardati; Arnis En Yulia (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Green beans (Vigna radiata L.) is a food which have a high nutrition, so many consumed by the people. The need of green beans in Indonesia increased in every year,while production of green beens in Indonesia not enough to cover the need of green beens in Indonesia. The research aims to know the effect of ameliorant and the number of earthworms to growth and yields of green beans, and to get the right combination to increase the growth and yields of green bean. This research was implemented in the green house Technical Service Unit (UPT),Faculty of Agricultur Riau University. This research use the complete random design(RAL)that was arrangement two factors and three repeat. The first factor is three level of ameliorant and the second factor is four level number of earthworm. The parameter of observation is plant height, diameter of stem, number of primary branch, flower appearance age, harvest age, the number of pods per plant, the number of dryseeds per plant and the weight of dryseeds per plant. Giving of 10 ton.ha-1 chicken manure and 9 earthworms per plant show the better result to plant height, diameter of stem, number of primary branch, harvest age, the number of pods per plant, the number of dry seeds per plant and the weight of dry seeds per plant. Giving of 10 ton.ha-1 tofu compost and 3 earthworm per plant showed the better result to plant height, diameter of stem, number of primary branch, number of pods per plant, the number of dryseeds per plant and the weight of dry seeds per plant. Keywords : green beans, earthworms, chicken manure, tofu compos